Evaluation of a prevention programme efficiency for patients with fixed orthodontic appliances - Matić Sava; Ivanović Mirjana; Nikolić Predrag (Vojnosanitetski Pregled)
Background/Aim. Orthodontic treatment enables the establishment of functional occlusion and improvement of oral health, however, it increases the risk of periodontal disease development. The aim of this paper was to examine the efficiency of the applied programme for the prevention of gingivitis in children undergoing the fixed orthodontic appliance therapy and to determine the most efficient devices and techniques for maintaining oral hygiene during orthodontic treatment. Methods. The study included 80 patients of both genders - 60 patients comprised the experimental group and 20 patients comprised the control group. All of them were patients of the Clinic for Orthodontics at the School of Dentistry in Belgrade, aged between 13 and 18. The Silness-Löe Plaque Index (PI) was utilised for the assessment of oral hygiene quality and Silness-Löe Gingival Index (GI) and Mühlemann Papilla Bleeding Index (PBI) were utilised for the assessment of gingival state. Checkups were conducted as a single-blind study at the beginning and after the first, the third and the sixth month of the preventive and prophylactic programme. Results. During the observed period, a statistically significant change in PI, GI and PBI values was noticed (p < 0.005), as well as the difference in the dynamics of value changes during the periods between the observed groups. Conclusion. The preventive programme, applied to children undergoing the fixed orthodontic appliance therapy, had a positive effect both on oral hygiene quality and gingival state. The values of the examined parameters of the patients from the experimental group were significantly lower in comparison with those of the patients from the control group. The most efficient combination of devices for oral hygiene during orthodontic treatment was: a Curaprox CP5460 toothbrush, CD Ortho 60 orthodontic toothbrush and Curaprox CPS 14 interdental brush.